Beluga (Delphinapterus leucas) response to personal watercraft and motorized whale watching vessels in the Churchill River estuary - Ausen, Emma L.; Marcoux, Marianne; Chan, Wayne S.; Barber, David G. (Frontiers in Marine Science, 2022)
As interest in tourism and conservation grows worldwide, whale-watching has become a popular means of educating the public about wildlife conservation. The short-term impact of ecotourism industries on observed species has been widely studied with findings that indicate responses are most often behavior alterations or avoidance. Close vessel interactions with beluga whales (Delphinapterus leucas) are a major draw for whale-watching ecotourism in Churchill, Manitoba, Canada. As the Churchill River estuary and surrounding waters are assessed for a Marine Protected Area, information on the response of belugas to vessels are needed to inform management. To assess this, an oblique time-lapse camera system with a 5-minute photo interval was set up overlooking a section of the Churchill River estuary that is shared by belugas and tourist vessels. Measurements calculated from photos were used to compare the distance between belugas and kayaks, paddleboards, motorboats, and Zodiac whale-watching vessels. These distances were compared to an expected distribution generated from locations of belugas in photos without the presence of vessels. We found evidence that belugas are attracted to kayaks, avoid paddleboards, and are neutral regarding motorboats and Zodiacs. This is the first study to quantify the behavioral response of cetaceans to tourist vessels using a camera system and a distance-based analysis. Results could inform the development of a site-specific management system that accounts for beluga-vessel relationships.